Optimizing Unsold Inventory Decisions under the Newsvendor Model - Mechmech, Rihab; Harbi, Slim; Hadj-Alouane, Atidel B.; Sboui, Sami (International Journal of Supply Chain Management, 2025)
Unsold products represent a persistent operational and financial challenge for manufacturers, wholesalers, and retailers. This paper aims to address the problem of unsold inventory management by developing a decision-support framework for clearance strategies. Based on the newsvendor model, the proposed approach jointly optimises supply chain profit from regular market sales and clearance sales. The optimisation relies on a qualitative risk–performance assessment of alternative clearance strategies, incorporating managers’ industrial knowledge. A numerical illustration highlights the main drivers influencing the selection of an optimal clearance policy, namely acceptable risk levels, expected clearance revenues, and capacity constraints. The results provide actionable managerial insights and are synthesised into a practical decision-making approach to support practitioners in selecting effective clearance strategies. The proposed framework is applicable to both seasonal and non-perishable products.